PEMENUHAN HAK MATERNITAS PEKERJA PEREMPUAN DI PERSEROAN TERBATAS S BERDASARKAN INTERNATIONAL LABOUR ORGANIZATION (ILO) NOMOR 183 TAHUN 2000: Fulfillment Of Maternity Rights Of Female Workers At Pt. S Based On The International Labour Organization (Ilo) Convention Number 183 Of 2000 - Adellia Puan Maharani; Aji Wibowo (Reformasi Hukum Trisakti, 2025)
Maternity Rights are part of human rights and are inherent in women to obtain freedom from discrimination, equality, and harassment as regulated in the International Convention for the Protection of Maternity or ILO Convention Number 183 of 2000. Although Indonesia has established women's rights in the form of laws and regulations, the regulations are not in accordance with the standards set by the ILO, one of which is at PT. S. In the treatment of pregnant workers, the ILO has established special regulations to protect employment status and workers' rights, one of which is maternity protection. The problem is, whether PT. S's actions towards one of its female workers regarding maternity leave rights are in accordance with the ILO Convention standards and how PT. S's efforts can fulfill the fulfillment of maternity rights for female workers based on the ILO Convention. This research is a normative research, with a descriptive analytical nature and drawing conclusions with deductive logic. The result is that the fulfillment of maternity leave rights for one of its female workers at PT. S is not in accordance with the standards in Article 3 of the ILO Convention Number 183 of 2000 in providing the duration of maternity leave and health insurance for the rights of female workers.